A video drowning detection device based on underwater computer vision. Issue 6 (23rd February 2023) - Liu, Tingzhuang; He, Xinyu; He, Linglu; Yuan, Fei
Abstract: Drowning is a significant public health concern. A video drowning detection algorithm is a helpful tool for finding drowning victims. However, there are three challenges that drowning detection research typically encounters: a lack of actual drowning video data, subtle early drowning traits, and a lack of real time. In this paper, the authors propose an underwater computer vision based drowning detection device composed of embedded AI devices, camera, and waterproof case to solve the above problems. The detection device utilizes the high‐performance computing of Jetson Nano to realize real‐time detection of drowning events through the proposed drowning detection algorithm on the acquired underwater video stream. The proposed drowning detection algorithm primarily consists of two stages: in the first step, to successfully solve the interference of the surroundings and to give a trustworthy basis for video drowning detection, the YOLOv5n network is used to detect the near‐vertical human body based on the characteristics of the drowning person. In the second stage, the authors propose a lightweight drowning detection network (DDN) based on a deep Gaussian model for fast feature vector detection. The lightweight DDN is combined with the Gaussian model to detect anomaly in the high‐level semantic features, which has higher robustness and solves the lack of drowning videos. The experimental results show that the proposed drowning detection algorithm has good comprehensive performance and practical application value. Abstract : In this paper, we propose an underwater computer vision based drowning detection device to realize real‐time detection of drowning events through the proposed drowning detection algorithm on the acquired underwater video stream. In the detection algorithm, we propose a lightweight drowning detection network (DDN) based on a deep Gaussian model for fast feature vector detection, which has higher robustness and solve the lack of drowning videos. The experimental results show that the proposed drowning detection algorithm has good comprehensive performance and great practical application value.